Tinjauan Fiqhi Muamalah Terhadap Sistem Bagi Hasil Nelayan dan Pemilik Bagang di Ujung Baru Kelurahan Polewali Kabupaten Polewali Mandar - Hamsiah Hamasah; M. Ali Rusdi (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2024)
A review of fiqhi muamalah on profit-sharing system between fishermen and boat owners in Polewali Mandar Regency. This research aims to understand the profit-sharing system and analyze the aspects of Islamic economic law related to it. The type of research used is field study with normative sociological approach and descriptive qualitative data. Data collection methods include observation, interviews, and documentation, while data analysis techniques include data identification, data presentation, and conclusion drawing. The results show that this profit-sharing system has been implemented by the community in Ujung Baru Village for several decades. In the review of Islamic economic law, this system falls under the mudharabah contract involving cooperation between both parties. The recommendation from this research is for boat owners to show or involve the records held during profit distribution to prevent misunderstandings among fishermen.